Allelic variation at the interleukin 1β gene is associated with decreased bone mass in patients with inflammatory bowel diseases. Issue 5 (1st November 2001) - Nemetz, A; Tóth, M; García-González, M A; Zágoni, T; Fehér, J; Peña, A S; Tulassay, Z
Abstract : BACKGROUND: Interleukin 1β (IL-1β) and its natural antagonist have been implicated in the pathogenesis of inflammatory bowel disease (IBD). Both cytokines influence bone formation. IL-1β stimulates osteoclast activity while interleukin 1 receptor antagonist (IL-1ra) enhances bone formation. AIMS: To determine whether the decreased bone mass in IBD is related to gene polymorphisms coding for IL-1β and IL-1ra, and thus identify patients with an increased risk. METHODS: Bone mineral densitometry was performed at the femoral neck, lumbar spine, and the distal third of the radius in 75 IBD patients (34 men/41 women; 40.3 (1.6) years) and in 58 healthy controls (HC; 28 men/30 women; 32.4 (1.2) years). Values were correlated with the Taq I and AvaI gene polymorphisms in the IL1B and the variable number of tandem repeats gene polymorphism in the IL1RN gene. RESULTS: In IBD patients, but not in HC, carriers of allele 2 at the AvaI gene polymorphism ( IL1B-511*2 ) had significantly lower Z scores at the lumbar spine (−0.82 (0.13) v −0.29 (0.21) p=0.03) and the femoral neck (−0.59 (0.14) v 0.15 (0.19); p=0.003) than non-carriers. These patients also had a higher risk for osteopenia or osteoporosis at the femoral neck (odds ratio 3.63 (95% confidence interval 0.95–13.93)). No association was found between bone mass and the other gene polymorphisms analysed in IBD patients or in HC. CONCLUSIONS: Our results suggest that genetic variability may be a major determinant of bone loss in IBD. Carriers of IL1B-511*2, who are hypersecretors of IL-1β, have a higher risk of presenting with low bone mass in IBD. Screening for this allele may contribute to determination of the risk of bone loss at the time of disease onset.